Features of the European Maritime Clusters - Regina Salvador; Abel Sim\~oes; Carlos Guedes Soares (European Regional Science Association (ERSA), 2015)
The paper analyses the national and regional European maritime clusters according to the sea basin division proposed by the European Union Integrated Maritime Policy: Atlantic and Arctic oceans; Baltic, Black, Mediterranean and North seas. Besides the identification of all maritime sectors by country ? be it at national and/or regional level - a statistical database is established per each and every of the above referred sea basins, in order that a comparative analysis can be developed. Also in line with Wijnolst, Jensen & Sødal (2003) that propose a maritime sector benchmarking - the ?Global Maritime Benchmarking? ? which should allow evaluating the maritime clusters evolution and strength - the paper estimates nine indicators: structural indicators (no. of clusters, no. of companies; no. of employees; no. of sectors; technological level; location); economic indicators (Gross Added Value, production; productivity; profit and rentability rates), internationalization (exports and imports, major clients and suppliers, international average prices, EU and third countries markets shares); critical mass (agglomerations and scale economies by maritime sector) and leader firms; level playing-field (free-competition, monopolistic, oligopolistic markets); innovation (major universities and R&D centers, no. patents, regional innovation systems); institutional framework (governance, connection with regional and national governments)and business networks; labour market (unemployment rate, average wages) and education (major schools and courses by different grades, training centers); and image and communication. Particular attention is attributed to the Atlantic basin strategy - the largest of all the EU Integrated Maritime Policy Basins ? where besides the Blue growth concerns the authors, develop the result of a group of interviews to experts on Blue Geopolitics and Geostrategic. The above comparison between sea basins will allow characterizing ?maritime Europe?, identifying the location of the main excellence centres and the major beneficiaries of the Integrated Maritime Policy decisions. The paper also suggest public strategies that would support clusters development ? or ?cluster enablers? ? that include, among others, the definition of an industrial policy, strengthening of demand pull sectors or the promotion of innovation, R&D and leader firms. The needed conditions in order that Europe could organise itself has a ?vast continental maritime cluster? are also under scrutiny.
Keywords: E20; F43; R10; 330; Maritime Clusters; Maritime Economy; EU Sea Basin Strategies